Coordinated in-home charging of plug-in electric vehicles from a household smart microgrid - Davydova, Anastasia; Chakirov, Roustiam; Vagapov, Yuriy; Komenda, Taras; Lupin, Sergey (2013 Africon, 2013)
Battery of a plug-in electric vehicle can be charged from a power grid at different locations. In case of charging at home location it performs a significant impact on household energy consumption and needs to be coordinated and scheduled in order to reduce peaks of power load and cost of electricity. This paper discusses coordination of in-home charging aimed to improve load factor and reduce cost of consumed energy. The algorithm of coordinated charging is based on prediction of household appliances load profile and used to control the electric vehicle battery charger. The simulation has been conducted to verify the proposed algorithm.